2
$\begingroup$

Let $G$ be a group. If $H\le G$ (notation for $H$ is a subgroup of $G$), then show that there is a homomorphism $\phi: G\to A(H\backslash G)$ and that $\ker\phi$ is the largest normal subgroup of $G$ contained in $H$. Here, $A(H\backslash G)$ denotes the set of all permutations on the set $H\backslash G$, of all right cosets of $H$ in $G$.

For simplicity, let $S := H\backslash G$ hereafter. We know that $S = \{Hg: g\in G\}$ where $Hg:= \{hg:h\in H\}$. Consider the following mapping which I claim is a homomorphism: $$\phi: G\to A(S), \phi: g\mapsto f_g$$ where $$f_g:S\to S, f_g: Hx\mapsto Hxg$$ $f_g$ is a bijection (permutation on $S$) because:

  1. Injective. $f_g(Hx) = f_g(Hy) \implies Hxg = Hyg$. This happens iff $xg(yg)^{-1}\in H$ which gives $xy^{-1}\in H$ and thus $Hx=Hy$.
  2. Surjective. Consider a right coset $Hx$. Clearly, $f_g(Hxg^{-1}) = Hxgg^{-1} = Hx$ showing surjectivity. Note that $xg^{-1}\in G$ since $G$ is a group, so $Hxg^{-1}$ is a valid right coset to choose.

I'm stuck while showing $\phi$ is a homomorphism because:

  1. Take $g,h\in G$. We want $\phi(gh) = f_{gh} = f_g\circ f_h = \phi(g)\phi(h)$, but: consider arbitrary $Hx\in G/H$. $f_{gh}(Hx) = Hxgh = (Hxg)h = f_h(Hxg) = f_h(f_g(Hx))$ which is $f_h\circ f_g$ and not what we need. Is this not the right homomorphism? What do I do?

  2. Certainly $\phi(g)$ is inside $A(S)$, so that is not a problem.

Lastly, I don't know what $\phi$ is yet (though intuition says it's closely related to the above stuff), leave alone $\ker\phi$. In the second part of the theorem, we want to show that $\ker\phi$ is the largest normal subgroup, i.e. any other normal subgroup of $G$ in $H$ is surely contained in $\ker\phi$. I hope this is easy to show once $\phi$ is known!

I'd appreciate any help, thank you!

$\endgroup$
4
  • $\begingroup$ $G/H$ normally denotes the set of left cosets $xH$ not right cosets. $\endgroup$
    – Derek Holt
    Feb 16 at 6:57
  • $\begingroup$ I'll fix that - I intend to work with right cosets. Is $H\backslash G$ the correct notation, or is it $G\backslash H$? $\endgroup$ Feb 16 at 6:59
  • $\begingroup$ Right cosets are $Hx$, so you need the $H$ on the left and the $G$ on the right, as in $H\backslash G$. The map you want is $f_g(Hx) = Hxg^{-1}$. $\endgroup$
    – Derek Holt
    Feb 16 at 8:31
  • $\begingroup$ Thanks! I'll keep that in mind. $\endgroup$ Feb 16 at 9:16
3
$\begingroup$

Let $g \in G$, and consider the mapping $\phi_g : S \to S$ given by $Hx \mapsto Hxg^{-1}$.

  • $\phi_g$ is injective, for if $Hxg^{-1} = Hyg^{-1}$, then$^\color{blue}1$ $xg^{-1}(yg^{-1})^{-1} = xy^{-1}$ is in $H$, but this means precisely that $Hx = Hy$.
  • $\phi_g$ is surjective, since $Hx = \phi_g(Hxg)$ for all $x \in G$.

Thus $\phi_g \in A(S)$ for each $g \in G$, and then the map $\phi : G \to A(S)$ given by $g \mapsto \phi_g$ is well-defined. Finally, $\phi$ is a group homomorphism: since $$(\forall x \in G) \quad \phi_{gh}(Hx) = Hx(gh)^{-1} = Hxh^{-1}g^{-1} = \phi_g(Hxh^{-1}) = \phi_g(\phi_h(Hx))$$ we have $\phi_{gh} = \phi_g \circ \phi_h$.


$^\color{blue}1$ Recall that $Na = Nb$ iff $ab^{-1} \in N$.

$\endgroup$
7
  • $\begingroup$ Could you please explain why: "...if $Hxg^{-1} = Hyg^{-1}$, then$^\color{blue}1$ $xg^{-1}(yg^{-1})^{-1} = xy^{-1}$ is in $H$..." - I had messed this part up in my attempt. $\endgroup$ Feb 16 at 8:28
  • $\begingroup$ The explanation for that part is in the footnote. Just put $N=H$, $a = xg^{-1}$ and $b = yg^{-1}$. Also note that $(yg^{-1})^{-1} = gy^{-1}$. $\endgroup$
    – azif00
    Feb 16 at 8:38
  • $\begingroup$ Thanks, that's helpful! Any thoughts on the second part, about $\ker\phi$? I know that $\ker\phi = \{g\in G: f_g = I\}$, i.e. we want $f_g(Hx) = Hxg^{-1} = Hx$ for all $Hx \in S$. $\endgroup$ Feb 16 at 9:17
  • $\begingroup$ Note that $$\begin{align} \ker \phi &= \{g \in G : (\forall x \in G) \ Hxg^{-1} = Hx\} \\ &= \{g \in G : (\forall x \in G) \ xg^{-1}x^{-1} \in H\} \\ &= \{g \in G : (\forall x \in G)(\exists h \in H) \ xg^{-1}x^{-1} = h\} \\ &= \{g \in G : (\forall x \in G)(\exists h \in H) \ g = x^{-1}h^{-1}x\} \\ &= \{g \in G : (\forall x \in G) \ g \in x^{-1}Hx\} \\ &= \bigcap_{x \in G} x^{-1}Hx (\subseteq e^{-1}He = H). \end{align}$$ Does this help? (I corrected some equalities). $\endgroup$
    – azif00
    Feb 16 at 9:38
  • 1
    $\begingroup$ @strawberry-sunshine And that completes the proof, well done! $\endgroup$
    – azif00
    Feb 16 at 18:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.